Structural and functional insights into the conductive pili of Geobacter sulfurreducens revealed in molecular dynamics simulations - Feliciano, G. T. [UNESP]; Steidl, R. J.; Reguera, G. (Royal Society of Chemistry, 2015)
Geobacter sulfurreducens (GS) electronically connects with extracellular electron acceptors using conductive protein filaments or pili. To gain insights into their role as biological nanowires, we investigated the structural dynamics of the GS pilus in solution via molecular dynamics simulations. In the model, all of the pilin's aromatics clustered as a right-handed helical band along the pilus, maintaining inter-aromatic distances and dimer configurations optimal for multistep hopping. The aromatics were interspersed within the regions of highest negative potential, which influenced the type and configuration of the aromatic contacts and the rates of electron transfer. Small foci of positive potential were also present but were neutralized within uncharged regions, thus minimizing charge trapping. Consistent with the model predictions, mutant strains with reduced aromatic contacts or negative potentials had defects in pili functions such as the reduction of Fe(III) oxides and electrodes. The results therefore support the notion of a pilus fiber evolved to function as an electronic conduit between the cell and extracellular electron acceptors.